2019
DOI: 10.33155/j.ramd.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Coaches’ and Young soccer players' training load perceptions during different training phases

Abstract: Objective: To our Knowledge, information about the agreement between coaches’ and the young soccer players’ session rating of perceived exertion is not consistent during specific periods of training (intensification and taper) and has not been established. The purpose of this study was to examine and compare the internal training load and session rating of perceived exertion between coaches’ and young soccer players’ during three weeks in different training phases. Method: Participants were 16 male elite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Interestingly, no substantial differences among coaches in the magnitude of this agreement were found. Concerning RPE, a number of previous studies, including a review and meta-analysis, reported no considerable differences between athletes' and coaches' perception 7,[55][56][57] ; other studies, however, reported a lack of correspondence. [58][59][60] A discrepancy between the sRPE of elite junior tennis players and international coaches was also reported.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, no substantial differences among coaches in the magnitude of this agreement were found. Concerning RPE, a number of previous studies, including a review and meta-analysis, reported no considerable differences between athletes' and coaches' perception 7,[55][56][57] ; other studies, however, reported a lack of correspondence. [58][59][60] A discrepancy between the sRPE of elite junior tennis players and international coaches was also reported.…”
Section: Discussionmentioning
confidence: 94%